Mechanical, durability and microstructural characteristics of Portland pozzolan cement (PPC) produced with high volume pumice: Green, cleaner and sustainable cement development. (16th May 2023) - Ulusu, Hayati; Yılmaz Aruntaş, Hüseyin; Burcu Gültekin, Arzuhan; Dayı, Mustafa; Çavuş, Murat; Kaplan, Gokhan
Graphical abstract: Highlights: The hygroscopic moisture of the pumice made grinding difficult. The use of more than 20% pumice significantly reduced the mechanical properties. Thanks to the use of pumice, the sulfate resistance of the mortars has increased. As the pumice ratio increased, the CO2 emissions of the cement could be reduced by more than 30%. It has been shown that producing sustainable cement using pumice is possible. Abstract: Nowadays, it is frequently preferred to use pozzolans instead of clinker to reduce the CO2 emissions that increase with cement production. Because in the future, the release of artificial pozzolans, such as fly ash and blast furnace slag, will decrease. Therefore, the demand for natural pozzolanic cement will increase. This study aimed to produce Portland Pozzolan Cement (PPC) by using pumice instead of clinker up to 40%. The Chemical, physical, mechanical, durability, microstructure, and carbon footprint characteristics of PPCs were investigated experimentally. As the pumice volume in the PPCs increased, the CaO/SiO2 ratio and specific gravity decreased. Due to the hygroscopic moisture of the pumice, its grindability has become difficult. While the 40 µm sieve residue of PPCs ranges from 0.8 to 1.7%, the sieve residue ratio generally increases as the pumice volume increases. The porous structure of pumice led to an increase in Blaine fineness as the replacement ratio increased. The Blaine fineness of PPCs containing 40% pumice rose by about 20% more than the reference cement. The consistency water of PCs varies between 29 and 36%. As the water consistency increased, the setting time of the pastes was prolonged. Initial setting times of PPCs are between 150 and 220 min. If the CaO/SiO2 ratio decreased with the pumice volume, the compression strength of the mortars decreased. While the 28-day compression strength of PPC containing 10% pumice was measured as 36.2 MPa, this value was measured as 21.6 MPa for PPC containing 40% pumice. As the pumice volume increased, the mortars' drying shrinkage and sulfate-induced expansion values decreased significantly. According to the sustainability analysis, the CO2 emissions of cement vary between 518 and 880 kg CO2 /t. By using pumice instead of clinker, CO2 emissions of cement can be reduced. In SEM examinations, it was determined that pumice concentrated the microstructure. As a result, it has been determined that eco-friendly cement can be obtained by using 10% and 20% pumice in PPC production.